Insects as bioindicator of environmental changes and pollution: Its monitoring and conservation - Priya, V; Mandal, Sunil Kumar; Dubey, Vinod Kumar; Patel, Deepak Kumar; Dwivedi, Shripati; Dube, Alok (Indian Farming, 2024)
A bioindicator is a living organism, such as an insect, a microbe, a plant, or an animal, used to monitor an ecosystem's health. In addition to being used to assess environmental health, environmental impacts of bio-geographic changes can also be assessed by them. As an indicator of the health of a biological system, each organic entity within it provides information about its surroundings, such as insects, which respond rapidly to environmental changes, are important biomarkers used to assess air, water, and soil quality, and as indicators of pollution. Environmental bioindicators can be obtained from many insect species, including several appropriate species for this group. As bioindicators and biomonitoring methods are becoming more popular, insects can be used to study the effects of external factors on ecosystems. These bioindicator insect species also aid in conserving the biodiversity of different species of flora and fauna and help the environment to keep them pollution free.